An analysis of policies for cotrimoxazole, amoxicillin and azithromycin use in Namibia's public sector: Findings and therapeutic implications. Issue 2 (16th January 2017) - Kibuule, Dan; Mubita, Mwangana; Naikaku, Ester; Kalemeera, Francis; Godman, Brian B.; Sagwa, Evans
Summary: Background: Despite Namibia's robust medicine use systems and policies, antibiotic use indicators remain suboptimal. Recent medicine use surveys rank cotrimoxazole, amoxicillin and azithromycin (CAA) among the most used medicines. However, there is rising resistance to CAA (55.9%‐96.7%). Unfortunately, to date, there have been limited studies evaluating policies to improve antibiotic use in Namibia. Aim: To evaluate public sector pharmaceutical policies and guidelines influencing the therapeutic use of CAA antibiotics in Namibia. Methods: Evaluate Namibia's pharmaceutical policies and guidelines for CAA use through quantitative text analysis. The main outcome variables were the existence of antibiotic policies, therapeutic indications per antibiotic and the type/level of healthcare facility allowed to use the antibiotic. Results: Policies for antibiotic use were limited, with only the draft Namibia Medicines Policy having a statement on antibiotic use. Several essential antibiotics had no therapeutic indications mentioned in the guidelines. Twenty‐nine antibiotics were listed for 69 therapeutic indications; CAA (49.3%) antibiotics and ATC J01C/J01D (48%) having the highest indications per antibiotic. For CAA antibiotics, this suggested use was mainly for acute respiratory infections (n=22, 37.2%). Published policies (58.6%—17/29) recommended antibiotics for use at the primary healthcare (PHC) level, with CAA antibiotics recommended mostly for respiratory tract infections and genitourinary infections. Conclusions: Policy and guidelines for antibiotic use in Namibia are not comprehensive and are skewed towards PHCs. Existing policies promote the wide use of CAA antibiotics, which may inadvertently result in their inappropriate use enhancing resistance rates. This calls for the development of more comprehensive antibiotic guidelines and essential medicine lists in tandem with local antimicrobial resistance patterns. In addition, educational initiatives among all key stakeholder groups.